Moringa oleifera hydorethanolic leaf extract induced acute and sub-acute hepato-nephrotoxicity in female ICR-mice - Aliyu, Abdullahi; Shaari, Mohd Rosly; Ahmad Sayuti, Nurul Syahirah; Reduan, Farhan Hanif; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin; Shaari, Khozirah; Hamzah, Hazilawati (SAGE Publications, 2021)
Moringa oleifera (M. oleifera) Lam belongs to the family Moringaceae. It is an important multipurpose tree that is largely distributed globally and has been used almost in every aspect of traditional medicine for the treatment of various illnesses including cancers, diabetes mellitus, asthma, arthritis, etc. This study investigated the effects of oral acute and sub-acute administration of M. oleifera hydroethanolic leaf extract (MOHE) in ICR-mice. Its major phenolic compounds were also determined. Ten (10) female, 8-week old mice were grouped into control and treatment groups for acute toxicity study. A dose of 2000 mg/kg MOHE was given once to the treatment group via oral gavage. However, for the sub-acute toxicity study, 25 mice were grouped into groups A (control), B (125 mg/kg), C (250 mg/kg), D (500 mg/kg) and E (1000 mg/kg). MOHE was given via oral gavage to groups B, C, D and E daily for 28 days. Group A received only distilled water. The mice were sacrificed at the end of the experiments and samples were collected for evaluation. The results of the chemical profiling of MOHE revealed the presence of glucomoringin, niaziminine, quercetin and kaempferol as the major compounds. The treated mice in the acute toxicity study were slightly anaemic and showed evidence of stress leukogram. Moreover, a slight increase in creatinine, significant increases in AST and CK, hepatic degeneration and necrosis, none-obstructive sinusoidal dilatation, renal tubular necrosis, interstitial nephritis and renal interstitial oedema were observed. It is concluded that the LD50 of MOHE is higher than 2000 mg/kg. However, oral administration of MOHE causes acute mild anaemia and moderate hepato-nephrotoxicity in ICR-mice. Its major phenolic compounds are glucomoringin, niaziminine, quercetin and kaempferol.